Screening of grape genotypes for aluminum tolerance and evaluation on selecting indices. Issue 4 (3rd July 2020) - Zhang, Yongfu; Xu, Shiqin; Mo, Liling
ABSTRACT: Grape is intolerant of aluminum. This intolerance leads to severe aluminum poisoning when the plants are cultivated in acidic soil, resulting in a decline in their yield and quality. To reduce and prevent the dangers of aluminum toxicity to grape, a method of identifying tolerance to aluminum was discussed, and genotypes tolerant to aluminum were screened. Twenty-six grape germplasm resources from different sources were used as materials. The morphological and physiological indices in different germplasm sources grown in soilless cultivation and subjected to aluminum stress were measured and compared to a control. The coefficient for the tolerance to aluminum of each character was used as the index of aluminum tolerance. The principal component analysis method was used to combine 13 individual indices into five independent comprehensive indices, which could represent 85.341% of the original data on the tolerance of the plants to aluminum. Through cluster analysis, the 26 grape germplasm sources were divided into three types. Vitis vinifera 'Red Globe', V. vinifera 'Blackcurrant', ( V. amurensis × V. vinifera ) ×V. amurensis 'Zuoyouhong' and V. sinocinerea were tolerant to aluminum. Twelve genotypes were moderately tolerant to aluminum and ten genotypes were intolerant to aluminum. Four indices with significant effects on the tolerance to aluminum were screened out, including the fresh weight of the aboveground vegetation and the malondialdehyde (MDA), H2 O2 and proline contents, which could be used as the identified index of the tolerance to aluminum in grape. The comprehensive evaluation of the tolerance of grape to aluminum using these methods can avoid the one-sidedness and instability of a single index, and the result is more reliable.